Pengaruh Flash Sale dan Taglineâ€œGratis Ongkirâ€ Shopee Terhadap Impulsive Buying Secara Online dengan Muslim Self-Control Sebagai Variabel Moderating (Kajian Perspektif Ekonomi Islam) - Dila Anggraini; Heru Aulia Azman; Nurul Fadhila Hasanah; Habil Febrian; Anwar Sholihin (Jurnal Ilmiah Ekonomi Islam, 2023)
This study was conducted with the aim of knowing and analyzing the Effect of Flash Sale and Shopee's "Free Shipping" Tagline on Impulsive Online Buying with Muslim self-control as Moderating Variable. The object of this research is the students of the Islamic Economics and Business Faculty at UIN Sjech M. Djamil Djambek Bukittinggi. This research is a quantitative research. The method used for sampling is using purposive sampling technique. In this study, data were collected by distributing questionnaires to 96 students of the Islamic Economics and Business Faculty, UIN Sjech M. Djamil Djambek Bukittinggi. The data analysis technique used is SmartPLS 3.3.9. The results of this study indicate that: 1) Flash sale has a positive effect on impulsive buying. 2) The tagline "free shipping" has a positive effect on impulsive buying. 3) Muslim self-control has a positive effect on impulsive buying. 4) Muslim self-control is not able to moderate the effect of flash sales on impulsive buying. 5) Muslim self-control is able to moderate the influence of the "free shipping" tagline on impulsive buying.